Comparative Analysis of the Universal Declaration of Human Rights (1948) and Nigerian Constitution (1999): Implications for Democratic Governance and Citizenship Education in Nigeria - Okunloye, Rotimi William (NIU Journal of Humanities, 2018)
The United Nations’ Universal Declaration of Human Rights (UDHR) (1948) is an internationally recognized frame of reference on human right constitutional provisions, observance, violations and advocacy. Therefore, an attempt is made in this paper, to undertake a comparative analysis of the human rights provisions in the Nigerian Constitution (1999) and the UDHR (1948). The paper reveals some similarities and difference between the two documents. It also observes some significant deficiencies in the Nigerian Constitution (1999) with reference to human rights provision in terms of scope of coverage, types of rights, jurisdiction or framework of application, grounds of just violation, and language of entrenchment. The implications of the observed deficiencies were also highlighted for civil liberty and democracy. The paper recommends that the Nigerian constitution be amended to conform with the internationally recognized benchmark of constitutional democracy by amending the Nigerian constitutional (1999) to entrench additional provisions of human right aside the existing civic-political rights; enhanced citizenship education in the school system and adult education programmes as well as socialization into sustainable democratic culture and governance; and improved human rights education in the basic school system and adult education programmes for citizenship education.